Faktor-Faktor yang Mempengaruhi Kepuasan Karyawan Kantoran Serta Dampaknya pada Niat untuk Menggunakan Ulang Layanan Aplikasi Go- Food di Pontianak - Hitten, Akhmad; Susanto, Arief (Fakultas Ekonomi dan Bisnis, UNTAN, 2019)
The objectives of this research are to test the effect of peceived of usefullness, perceived ease of use, perceived of price on the intention to reuse the application Go Food, mediated by consumer satisfaction. The samples of the research were have been selected by using purposive sampling which is taking sample based on characteristics and the objective of the study. The data from this research is analyzed with WarpPLS by applying Structual Equation Model (SEM). The hypothesis is tested by using WarpPLS 6.0 program. The result shows that the perceived usefulness and perceived of price is has significant effect on consumer satisfaction whereas perceived ease of use do not have effect on consumer satisfaction, and consumer satisfaction is significantly effect on intention to reuse the application of Go-Food.